Evaluating the impacts of an improved sewer system on city flood inundations using MIKE Urban Model - Thuy Kim Doan, Phuong; Cuong Le, Xuan; Thao Le, Van; Némery, Julien (Vietnam Journal of Earth Sciences, 2023)
Urbanization is an objective law of socioeconomic development. However, the drainage system is incompatible with the development of urban areas and the increasing population. Some sewer lines are built or added, but they are not synchronized and poorly sloped with debris and inadequate cross-sectional areas, leading to local flooding. In this study, we applied and locally optimized the Mike Urban model to the sewer network in Da Nang City to evaluate the inundation capability as well as the current and future sewer system capacity. The model was calibrated and validated at three typical sites for the data on October 16 and November 7, 2011; evaluated for the heavy rain data on October 14, 2022; and tested scenarios for 2030. The results showed that during heavy rain on October 14, 2022, many urban areas of Da Nang City were crowded, and the number of flooded manholes along the river suddenly increased dramatically because of the high water level and low ground level, which was impossible for rainwater to flow into the river during the high tide. The study also revealed that the planning for the drainage system until 2030 has improved the water drainage situation in the city by adjusting and adding some drainage systems. While this region remains poorly studied, this study brings original information that will help stakeholders to adopt appropriate strategies for the management of their cities that experience critical inundation.